Air cathode catalyst NiCo2S4 / CS and preparation method and application thereof

The NiCo2S4/CS catalyst, with a three-dimensional porous rod-shaped carbon sponge support, addresses the cycle stability issue in zinc-air batteries, achieving a 318-hour cycle life and reduced polarization with its non-precious metal composition.

CN119208633APending Publication Date: 2024-12-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411337925.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The cycle stability of cathode catalysts in zinc-air batteries restricts their cycle life, and the use of precious metal catalysts is scarce and difficult to scale.

Method used

A non-precious metal oxygen reduction catalyst, NiCo2S4/CS, is developed, comprising a three-dimensional porous rod-shaped carbon sponge with NiCo2S4 nanocrystalline particles supported on its surface, prepared through a specific method involving hydrothermal reactions and etching processes.

Benefits of technology

The NiCo2S4/CS catalyst maintains good electrocatalytic performance, extends the cycle life of zinc-air batteries to 318 hours with reduced electrochemical polarization, and is suitable for zinc-air batteries due to its excellent cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208633A_ABST
    Figure CN119208633A_ABST
Patent Text Reader

Abstract

The invention discloses an air cathode catalyst NiCo2S4 / CS as well as a preparation method and application thereof, and relates to the technical field of electrochemistry. In the invention, the air cathode catalyst NiCo2S4 / CS comprises a three-dimensional porous rod-shaped carbon sponge CS and NiCo2S4 nanocrystal particles loaded on the three-dimensional porous rod-shaped carbon sponge CS. When the air cathode catalyst NiCo2S4 / CS prepared by the invention is used as a cathode material of a zinc air battery, the zinc air battery can have excellent cycling stability and relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to an air cathode catalyst NiCo2S4 / CS and a preparation method and application thereof. Background Art

[0002] Zinc-air batteries (ZABs) have attracted much attention from researchers due to their high specific energy, environmental friendliness and high safety, and are considered to be the most promising energy storage devices in the future. However, since the cycle stability of the cathode catalyst of zinc-air batteries (ZABs) will restrict the cycle life of zinc-air batteries (ZABs), the prior art generally uses precious metal catalysts with better cycle stability as cathode catalytic oxygen reduction reactions. However, precious metal catalyst resources are scarce and difficult to apply on a large scale. Therefore, the present application has developed a non-precious metal oxygen reduction catalyst with good cycle stability - spinel structured sulfide NiCo2S4 / CS. Summary of the invention

[0003] In order to make up for the deficiencies of the prior art, the present invention provides an air cathode catalyst NiCo2S4 / CS and a preparation method and application thereof.

[0004] In order to achieve the above object, the technical solution of the present invention is:

[0005] An air cathode catalyst NiCo2S4 / CS comprises a three-dimensional porous rod-shaped carbon sponge CS and NiCo2S4 nanocrystalline particles supported on the three-dimensional porous rod-shaped carbon sponge CS.

[0006] Preferably, the three-dimensional porous rod-shaped carbon sponge CS has a rod-shaped structure with pores; the NiCo2S4 nanocrystalline particles are loaded on the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS.

[0007] A method for preparing an air cathode catalyst NiCo2S4 / CS comprises the following steps:

[0008] S1. dissolving aluminum nitrate nonahydrate and 1,4-naphthalenedicarboxylic acid in deionized water to obtain solution I;

[0009] S2, ultrasonically homogenizing solution I and then performing a hydrothermal reaction to obtain a mixture A;

[0010] S3, centrifuging the mixture A to obtain a light yellow precipitate, washing the light yellow precipitate and vacuum drying it to obtain a dried precipitate;

[0011] S4, calcining the dried precipitate under a nitrogen atmosphere to obtain a rod-shaped aluminum-based metal organic framework precursor;

[0012] S5, mixing a rod-shaped aluminum-based metal organic framework precursor with hydrofluoric acid, and ultrasonically etching for 40 minutes to obtain a mixture B; centrifugally washing the mixture B to obtain a neutral aluminum-based metal organic framework, and drying the neutral aluminum-based metal organic framework to obtain a three-dimensional porous rod-shaped carbon sponge CS;

[0013] S6, ultrasonically dispersing the three-dimensional porous rod-shaped carbon sponge CS in a mixed solution obtained by mixing ethanol and deionized water to obtain solution II; adding cobalt acetate tetrahydrate and nickel acetate tetrahydrate to solution II, and then heating and stirring under condensation reflux conditions, and then adding ammonia water, and continuing to stir under condensation reflux conditions to obtain solution III;

[0014] S7. Add thiourea to solution III, continue stirring under condensation reflux conditions to obtain solution IV; subject solution IV to a hydrothermal reaction to obtain a mixture C, and then, centrifuge and wash the mixture C, and then freeze-dry it for 24 hours to obtain an air cathode catalyst NiCo2S4 / CS.

[0015] Preferably, in step S4, before calcining the dried precipitate under a nitrogen atmosphere, the dried precipitate is first ground into powder to obtain precipitate powder, and then the precipitate powder is calcined under a nitrogen atmosphere.

[0016] Preferably, in step S1, in solution I, the molar ratio of aluminum nitrate nonahydrate, 1,4-naphthalene dicarboxylic acid and deionized water is (1-3):(0.5-2):(1000-1200).

[0017] Preferably, in step S2, the temperature of the hydrothermal reaction is 150°C to 180°C.

[0018] Preferably, in step S5, the mass percentage concentration of hydrofluoric acid is 5% to 10%.

[0019] Preferably, in step S6, the volume ratio of ethanol to deionized water is (55-60):(2-4), the mass percentage concentration of ethanol is 99.5%; the molar ratio of cobalt acetate tetrahydrate, nickel acetate tetrahydrate and thiourea is (1-3):(0.5-2):(5-7); and the mass percentage concentration of ammonia water is 25%-28%.

[0020] Preferably, in step S6, the heating and stirring temperature is 60°C to 80°C.

[0021] Preferably, in step S7, the temperature of the hydrothermal reaction is 150°C to 180°C.

[0022] Application of air cathode catalyst NiCo2S4 / CS as cathode catalyst in zinc-air batteries.

[0023] A method for preparing a zinc-air battery using an air cathode catalyst NiCo2S4 / CS comprises the following steps:

[0024] a) Preparation of cathode catalyst: Nafion ethanol solution, air cathode catalyst NiCo2S4 / CS and conductive carbon are mixed, and then ultrasonically treated to obtain cathode catalyst suspension;

[0025] b) Preparation of air cathode: Place carbon paper on a constant temperature heating pad, spray the cathode catalyst suspension prepared in step S1 on the hydrophilic layer of the carbon paper, and let it stand for a period of time to obtain an air cathode;

[0026] c) Preparation of electrolyte: Mix deionized water, KOH solution and zinc acetate solution, and stir until dissolved to obtain an electrolyte for a zinc-air battery;

[0027] d) Assembly of zinc-air battery: Assemble the zinc-air battery mold, air cathode, zinc sheet anode electrode and electrolyte together to obtain the zinc-air battery.

[0028] Preferably, in step a), the ratio of the volume μL of the nafion ethanol solution to the mass mg of the air cathode catalyst NiCo2S4 / CS is (700-800):(2-4); the mass ratio of the air cathode catalyst NiCo2S4 / CS and the conductive carbon is (2-4):(0.5-1.5), the mass percentage concentration of ethanol in the nafion ethanol solution is 0.1%, and the mass percentage concentration of the ethanol solution is 0.1%.

[0029] Preferably, in step b), the cathode catalyst suspension is evenly and slowly sprayed onto the hydrophilic layer of the carbon paper, and the catalyst content on the carbon paper is 1 mg / cm 2 .

[0030] Preferably, in step b), the standing time is 0.5 h to 1 h.

[0031] Preferably, in step c), the ratio of the volume mL of deionized water to the mass g of KOH is (40-60):(13.5-20.2); the mass ratio of KOH to zinc acetate is (13.5-20.2):(1.47-2.20); the mass percentage concentration of the KOH solution is 6 mol / L, and the mass percentage concentration of the zinc acetate solution is 0.2 mol / L.

[0032] Preferably, in step d), the zinc-air battery mold is a plexiglass mold, and step d) specifically comprises the following steps:

[0033] First, place the plexiglass mold in alcohol and ultrasonically clean it for 1 to 2 minutes, then rinse it clean and dry it for later use;

[0034] Then, the air electrode and the zinc sheet anode electrode are fixed in the above-mentioned organic glass mold respectively, and the air electrode and the zinc sheet anode electrode are separated by a rubber ring; then, the electrolyte prepared in step c) is injected into the organic glass mold to obtain a zinc-air battery.

[0035] A zinc-air battery is prepared by the method for preparing a zinc-air battery using an air cathode catalyst NiCo2S4 / CS.

[0036] Compared with the prior art, the beneficial technical effects of this application are:

[0037] In the present application, aluminum nitrate nonahydrate and 1,4-naphthalenedicarboxylic acid are dissolved in deionized water, and then under the action of hydrothermal reaction, Al 3+ Replace H in 1,4-naphthalenedicarboxylic acid + The mixture A is centrifuged, washed, dried, and then calcined to obtain a rod-shaped aluminum-based metal organic framework precursor, and then the aluminum-based metal organic framework precursor is etched with hydrofluoric acid to make the Al in the aluminum-based metal organic framework precursor 3+ The mixture B is etched away by hydrofluoric acid to obtain a mixture B, which is then centrifugally washed and dried to obtain a three-dimensional porous rod-shaped carbon sponge CS; the three-dimensional porous rod-shaped carbon sponge CS is then mixed with ethanol and deionized water so that the three-dimensional porous rod-shaped carbon sponge CS can be well dispersed in a liquid environment composed of ethanol and deionized water to obtain a solution II, and then the solution II is mixed with cobalt acetate tetrahydrate and nickel acetate tetrahydrate and then heated, and then ammonia water is added to form a hydroxyl compound; then the solution III having the hydroxyl compound is mixed with The thiourea is mixed and then subjected to a hydrothermal reaction. In the hydrothermal reaction stage, the thiourea is first hydrolyzed to generate H2S, as shown in the following formula: NH2CSNH2+4H2O→2NH3·H2O+H2S+CO2. Then, the generated H2S reacts with the hydroxyl compound in solution IV to generate NiCo2S4 particles. Then, NiCo2S4 is loaded on the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS through the multi-electron pair effect under the action of the hydrothermal reaction to obtain the spinel sulfide NiCo2S4 / CS.

[0038] The air cathode catalyst NiCo2S4 / CS prepared in the present application inherits the good electrocatalytic performance of the sulfide NiCo2S4, and maintains the porous rod-like structure and excellent electrical conductivity of the three-dimensional porous rod-like carbon sponge CS; moreover, it can be seen from the test that the three-dimensional porous rod-like carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 of the present application is loaded with an appropriate amount of sulfide NiCo2S4, and the sulfide NiCo2S4 is relatively evenly loaded on the surface and gaps of the three-dimensional porous rod-like carbon sponge CS with a porous rod-like structure, and there is no large-scale aggregation of sulfide NiCo2S4 nanocrystal particles. The zinc-air battery (i.e., the zinc-air battery obtained by Application Ⅰ) using the air cathode catalyst NiCo2S4 / CS prepared in Example 1 as the cathode catalyst in the present application obtains a longer stable cycle time, and the cycle life of the zinc-air battery can reach 318 hours.

[0039] In addition, it can be seen from the test that when the air cathode catalyst NiCo2S4 / CS prepared in the present application is used as the cathode material of the zinc-air battery, the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery is reduced by at least only about 0.029V, and the cycle life of the zinc-air battery can be extended to 318 hours at most, which shows that when the air cathode catalyst NiCo2S4 / CS prepared in the present application is used as the cathode material of the zinc-air battery, the zinc-air battery can have excellent cycle stability and a longer life, that is to say, the air cathode catalyst NiCo2S4 / CS prepared in the present application is very suitable for the field of zinc-air batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope (SEM) image of the air cathode catalyst NiCo2S4 / CS prepared in Example 1;

[0041] Figure 2 is an X-ray diffraction (XRD) pattern of the air cathode catalyst NiCo2S4 / CS prepared in Example 1;

[0042] Figure 3 This is a SEM image of the air cathode catalyst NiCo2S4 / CS prepared in Example 2;

[0043] Figure 4 is an X-ray diffraction (XRD) pattern of the air cathode catalyst NiCo2S4 / CS prepared in Example 2;

[0044] Figure 5 This is a SEM image of the air cathode catalyst NiCo2S4 / CS prepared in Example 3;

[0045] Figure 6is the X-ray diffraction (XRD) pattern of the air cathode catalyst NiCo2S4 / CS prepared in Example 3;

[0046] Figure 7 This is a SEM image of the sulfide NiCo2S4 prepared in Comparative Example 2;

[0047] Figure 8 is the XRD pattern of the sulfide NiCo2S4 prepared in Comparative Example 2;

[0048] Fig. 9 This is a SEM image of the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1;

[0049] Fig.10 is the XRD pattern of the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1;

[0050] Fig.11 BET test result graphs are performed for the air cathode catalyst NiCo2S4 / CS prepared in Examples 1 to 3, the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1, and the sulfide NiCo2S4 prepared in Comparative Example 2; wherein, Figure a is the adsorption-desorption curve of Example 1, Figure b is the adsorption-desorption curve of Example 2, Figure c is the adsorption-desorption curve of Example 3, Figure d is the adsorption-desorption curve of Comparative Example 1, and Figure e is the adsorption-desorption curve of Comparative Example 2;

[0051] Fig.12 Constant current charge and discharge curves obtained by constant current charge and discharge tests of the zinc-air batteries obtained in Application 1, Application 2, Application 3, Comparative Application I and Comparative Application II. DETAILED DESCRIPTION

[0052] The following examples are used to illustrate the effects of the method and catalyst of the present invention. The following examples are only used to illustrate the present invention, but are not used to limit the scope of the present invention. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0053] Embodiment 1:

[0054] A method for preparing an air cathode catalyst NiCo2S4 / CS comprises the following steps:

[0055] S1. Dissolve 0.75 g of aluminum nitrate nonahydrate and 0.216 g of 1,4-naphthalenedicarboxylic acid in 20 ml of deionized water to obtain solution I.

[0056] S2. After solution I is homogenized by ultrasonic treatment, it is placed in a reaction kettle, and then the reaction kettle is placed in an oven for hydrothermal reaction at a temperature of 180° C. and a time of 24 h to obtain a mixture A;

[0057] S3, centrifuging the mixture A to obtain a light yellow precipitate, washing the light yellow precipitate with deionized water, and then vacuum drying to obtain a dried precipitate; wherein the centrifugal speed is 9000 rpm, and the centrifugal operation time is 5 min;

[0058] S4, grinding the dried precipitate into powder to obtain precipitate powder, and calcining the precipitate powder at 800° C. for 5 h under a nitrogen atmosphere to obtain a rod-shaped aluminum-based metal organic framework precursor;

[0059] S5. Mix the rod-shaped aluminum-based metal organic framework precursor with 10 ml of hydrofluoric acid with a mass concentration of 10%, and ultrasonically etch for 40 minutes to obtain a mixture B; centrifuge and wash the mixture B with deionized water and ethanol to obtain a neutral aluminum-based metal organic framework, and dry the neutral aluminum-based metal organic framework at 80° C. for 12 hours to obtain a three-dimensional porous rod-shaped carbon sponge CS; wherein the centrifugal speed is 9000 rpm and the centrifugal washing time is 5 minutes;

[0060] S6, ultrasonically dispersing 0.102 g of three-dimensional porous rod-shaped carbon sponge CS in a mixed solution obtained by mixing 57 ml of ethanol (analytical grade) and 3 ml of deionized water to obtain solution II, wherein the ultrasonic time is 15 min; adding 0.1126 g of cobalt acetate tetrahydrate and 0.0571 g of nickel acetate tetrahydrate to solution II, and then heating and stirring at 80° C. under condensation reflux conditions for 2 h, and then adding 1 ml of ammonia water, the mass percentage concentration of ammonia water is 25%, and then continuing to stir under condensation reflux conditions for 2 h to obtain solution III;

[0061] S7. Add 0.1028 g of thiourea to solution III, continue stirring under condensation reflux conditions for 20 hours to obtain solution IV; subject solution IV to a hydrothermal reaction for 3 hours to obtain a mixture C, and the hydrothermal reaction temperature is 170°C; then, the mixture C is centrifugally washed with deionized water, and then freeze-dried for 24 hours to obtain an air cathode catalyst NiCo2S4 / CS; during the centrifugal washing process, the centrifugal speed is 9000 rpm and the time is 5 minutes.

[0062] from Figure 1It can be seen that the air cathode catalyst NiCo2S4 / CS prepared in Example 1 has a rod-like structure as a whole, and the rod-like structure has a large number of pores. Particles are loaded on the surface and pores of the rod-like structure, and the particles are relatively evenly dispersed, and there is less aggregation of particles. The above-mentioned rod-like structure is the structure of a three-dimensional porous rod-like carbon sponge CS, and the above-mentioned particles are NiCo2S4 nanocrystalline particles. Since there are many pores on the surface of the three-dimensional porous rod-like carbon sponge CS with a rod-like structure, the surface and pores of the three-dimensional porous rod-like carbon sponge CS provide a larger specific surface area for the attachment of NiCo2S4 nanocrystalline particles, which makes it easier for NiCo2S4 nanocrystalline particles to be adsorbed on the surface and pores of the three-dimensional porous rod-like carbon sponge CS.

[0063] Embodiment 2:

[0064] The difference between Example 2 and Example 1 is that in step S6, the amount of cobalt acetate tetrahydrate is 0.0375 g, the amount of nickel acetate tetrahydrate is 0.0190 g, and the amount of ammonia water is 0.33 ml; in step S7, the amount of thiourea is 0.0342 g.

[0065] By performing SEM testing on the air cathode catalyst NiCo2S4 / CS prepared in Example 2, a SEM image of the air cathode catalyst NiCo2S4 / CS prepared in Example 2 was obtained, as shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the air cathode catalyst NiCo2S4 / CS prepared in Example 2 is a rod-shaped structure as a whole, and the rod-shaped structure has a large number of pores. The surface and pores of the rod-shaped structure are loaded with particles, and the particles are dispersed relatively evenly, and there is less aggregation of particles. The above-mentioned rod-shaped structure is the structure of a three-dimensional porous rod-shaped carbon sponge CS, and the above-mentioned particles are NiCo2S4 nanocrystalline particles; because there are many pores on the surface of the three-dimensional porous rod-shaped carbon sponge CS in the rod-shaped structure, the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS provide a large specific surface area for the attachment of NiCo2S4 nanocrystalline particles. Compared with the air cathode catalyst NiCo2S4 / CS prepared in Example 1, the NiCo2S4 nanocrystalline particles loaded on the three-dimensional porous rod-shaped carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 2 are significantly less than the NiCo2S4 nanocrystalline particles loaded on the three-dimensional porous rod-shaped carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0066] Embodiment three:

[0067] The difference between Example 3 and Example 1 is that in step S6, the amount of cobalt acetate tetrahydrate is 0.2252 g, the amount of nickel acetate tetrahydrate is 0.1142 g, and the amount of ammonia water is 2.0 ml; in step S7, the amount of thiourea is 0.2056 g.

[0068] By performing SEM testing on the air cathode catalyst NiCo2S4 / CS prepared in Example 3, a SEM image of the air cathode catalyst NiCo2S4 / CS prepared in Example 3 was obtained. Figure 5 As shown. Figure 5 It can be seen that the air cathode catalyst NiCo2S4 / CS prepared in Example 3 is in a rod-like structure as a whole, and the rod-like structure has a large number of pores. The surface and pores of the rod-like structure are loaded with particles, and the particles are dispersed relatively evenly, and there is less aggregation of particles. The above-mentioned rod-like structure is the structure of a three-dimensional porous rod-like carbon sponge CS, and the above-mentioned particles are NiCo2S4 nanocrystalline particles; because there are many pores on the surface of the three-dimensional porous rod-like carbon sponge CS in a rod-like structure, the surface and pores of the three-dimensional porous rod-like carbon sponge CS provide a large specific surface area for the attachment of NiCo2S4 nanocrystalline particles. Moreover, compared with the air cathode catalyst NiCo2S4 / CS prepared in Example 1, the NiCo2S4 nanocrystalline particles loaded on the three-dimensional porous rod-like carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 3 are significantly more than the NiCo2S4 nanocrystalline particles loaded on the three-dimensional porous rod-like carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0069] Comparative Example 1:

[0070] Comparative Example 1 in the present application is used to prepare a three-dimensional porous rod-shaped carbon sponge CS, wherein the steps of preparing the three-dimensional porous rod-shaped carbon sponge CS in Comparative Example 1 are completely consistent with the steps of preparing the three-dimensional porous rod-shaped carbon sponge CS from step S1 to step S5 in Example 1.

[0071] The test results of the SEM test on the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1 are as follows: Figure 7 As shown. Figure 7 It can be seen that the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1 presents a typical rod-shaped structure, which is consistent with the rod-shaped structure of the three-dimensional porous rod-shaped carbon sponge CS in Example 1. This also shows that the rod-shaped structure in the air cathode catalyst NiCo2S4 / CS prepared in Examples 1 to 3 is the structure of the three-dimensional porous rod-shaped carbon sponge CS.

[0072] Comparative Example 2:

[0073] The sulfide NiCo2S4 prepared in Comparative Example 2 of the present application, wherein the sulfide NiCo2S4 prepared in Comparative Example 2 comprises the following steps:

[0074] Step 1): 0.1126 g of cobalt acetate tetrahydrate and 0.0571 g of nickel acetate tetrahydrate are added to solution II, and stirred at 80° C. for 2 h under condensation reflux conditions, and then 1 ml of ammonia water is added, the mass percentage concentration of ammonia water is 25%, and then, stirring is continued under condensation reflux conditions for 2 h to obtain solution A;

[0075] Step 2): Add 0.1028 g of thiourea to solution A, continue stirring under condensation reflux conditions for 20 hours to obtain solution C; subject solution C to a hydrothermal reaction for 3 hours at a hydrothermal reaction temperature of 170°C, and then centrifuge and wash with deionized water to obtain a primary sample, freeze-dry the primary sample for 24 hours to obtain sulfide NiCo2S4; wherein the centrifugal washing process is performed at a centrifugal speed of 9000 rpm for 5 minutes.

[0076] The present application conducted SEM test on the sulfide NiCo2S4 prepared in Comparative Example 2. The test results are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that the sulfide NiCo2S4 nanocrystalline particles exhibit a spinel structure, which also proves that the particles in the air cathode catalyst NiCo2S4 / CS prepared in Examples 1 to 3 are NiCo2S4 crystal particles.

[0077] XRD test:

[0078] 1) This application conducted an XRD test on the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1. The test results are as follows: Figure 8 As shown. Figure 8 It can be seen that the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1 has an obvious carbon peak, which is consistent with the peak structure of the carbon sponge in the prior art reported in the literature.

[0079] 2) The sulfide NiCo2S4 prepared in Example 2 of this application was subjected to XRD test. The test results are as follows: Fig.10 As shown, from Fig.10 It can be seen that the peak structure of the sulfide NiCo2S4 prepared in Comparative Example 2 is consistent with the peak structure of NiCo2S4 in the prior art reported in the literature.

[0080] 3) The present application conducted an XRD test on the spinel structure sulfide NiCo2S4 / CS prepared in Example 1. The test results are as follows: Figure 2 As shown. Figure 2It can be seen that the peak structure of NiCo2S4 in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 is consistent with the peak structure of the sulfide NiCo2S4 prepared in Comparative Example 2, indicating that the two samples have the same crystal structure. However, the characteristic peak intensity of the air cathode catalyst NiCo2S4 / CS prepared in Example 1 is different from that of the sulfide NiCo2S4 prepared in Comparative Example 2. This is mainly because the NiCo2S4 nanocrystalline particles in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 are loaded on the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS, resulting in a change in its XRD characteristic peak intensity.

[0081] 4) This application conducted an XRD test on the air cathode catalyst NiCo2S4 / CS prepared in Example 2. The test results are as follows: Figure 4 As shown. Figure 4 It can be seen that the peak structure of NiCo2S4 in the air cathode catalyst NiCo2S4 / CS prepared in Example 2 is consistent with the peak structure of the sulfide NiCo2S4 prepared in Comparative Example 2, which indicates that the NiCo2S4 in the air cathode catalyst NiCo2S4 / CS prepared in Example 2 has the same crystal structure as the NiCo2S4 prepared in Comparative Example 2.

[0082] 5) The present application conducted an XRD test on the air cathode catalyst NiCo2S4 / CS prepared in Example 3. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that the peak structure of NiCo2S4 in the air cathode catalyst NiCo2S4 / CS prepared in Example 3 is consistent with the peak structure of the sulfide NiCo2S4 prepared in Comparative Example 2, which indicates that the NiCo2S4 in the air cathode catalyst NiCo2S4 / CS prepared in Example 3 has the same crystal structure as the NiCo2S4 prepared in Comparative Example 2.

[0083] In addition, the present application also conducted BET tests on the air cathode catalyst NiCo2S4 / CS prepared in Examples 1 to 3, the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1, and the sulfide NiCo2S4 prepared in Comparative Example 2. The test results are as follows: Fig.11 And as shown in Table 1.

[0084]

[0085]

[0086] from Fig.11It can be seen that the pore sizes of the air cathode catalysts NiCo2S4 / CS prepared in Examples 1 to 3 are mainly concentrated in the range of 2 to 50 nm, belonging to mesoporous materials; and the hysteresis loops of their adsorption curves are all H4 type, indicating that the pores of these materials have the characteristics of a mixture of micropores and mesopores, which is consistent with the solid of crack pores, and corresponds exactly to the pores distributed on the rod-like structures of Examples 1 to 3.

[0087] It can be seen from Table 1 that the specific surface area of ​​the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1 is 1858.049 m 2 / g, and the pore volume is 0.998cm 3 / g, which shows that the three-dimensional porous rod-shaped carbon sponge CS prepared in comparative example 1 has a larger specific surface area and pore volume, and these larger specific surface area and pore volume can facilitate more NiCo2S4 nanocrystalline particles to adhere to the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS. In addition, it can be seen from Table 1 that the specific surface area and pore volume of the air cathode catalyst NiCo2S4 / CS prepared in Example 1 are smaller than the specific surface area and pore volume of the air cathode catalyst NiCo2S4 / CS prepared in Example 2, and the specific surface area and pore volume of the air cathode catalyst NiCo2S4 / CS prepared in Example 1 are larger than the specific surface area and pore volume of the air cathode catalyst NiCo2S4 / CS prepared in Example 3; this shows that the amount of sulfide NiCo2S4 loaded on the three-dimensional porous rod-shaped carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 of the present application is smaller than that in Example 2, and larger than that in Example 3.

[0088] Application of spinel structure sulfide NiCo2S4 / CS:

[0089] Application 1:

[0090] A method for preparing a zinc-air battery using the air cathode catalyst NiCo2S4 / CS described in Example 1 comprises the following steps:

[0091] a) Preparation of cathode catalyst: 750ul of nafion ethanol solution, 3mg of the air cathode catalyst NiCo2S4 / CS prepared in Example 1 and 1mg of conductive carbon were mixed, and then ultrasonically treated for 30min to obtain a cathode catalyst suspension, wherein the mass percentage concentration of ethanol in the nafion ethanol solution was 0.1%;

[0092] b) Preparation of air cathode: Take a piece of 3cm 2The carbon paper was placed on a constant temperature heating pad at 70°C, and the cathode catalyst suspension prepared in step S1 was added to the spray gun, and then evenly and slowly sprayed on the hydrophilic layer of the carbon paper. The carbon paper was left to stand for 30 minutes, so that the catalyst content on the carbon paper was 1 mg / cm 2 , obtaining an air cathode;

[0093] c) Preparation of electrolyte: 50 ml of deionized water, 19.8 g of KOH solution (the molar concentration of KOH solution is 6 mol / L) and 2.21 g of zinc acetate solution (0.2 mol / L of zinc acetate solution) are mixed and stirred until dissolved to obtain an electrolyte for a zinc-air battery;

[0094] d), assembling a zinc-air battery mold, an air cathode, a zinc sheet anode electrode and an electrolyte together to obtain a zinc-air battery; specifically, in step d), the zinc-air battery mold is a plexiglass mold, and step d) specifically includes the following steps:

[0095] First, the organic glass mold is placed in alcohol, ultrasonically cleaned for 1 to 2 minutes, then rinsed and dried for standby use; then, the air electrode and the zinc sheet anode electrode are respectively fixed in the above-mentioned organic glass mold, and the air electrode and the zinc sheet anode electrode are separated by a rubber ring; then, the electrolyte prepared in step c) is injected into the organic glass mold to obtain a zinc-air battery.

[0096] The zinc-air battery obtained in the present application is charged and discharged at 10 mA·cm -2 The zinc-air battery was tested for constant current charge and discharge at a current density of Fig.12 and as shown in Table 2; among them, Fig.12 The stable cycle time of the constant current charge and discharge curve shown is used to characterize the cycle stability of the zinc-air battery. 初 Indicates the initial voltage difference, which refers to the voltage difference during the first charge and discharge, ΔE 末 It represents the final voltage difference, which indicates the voltage difference of the material at the 600th charge and discharge. Moreover, the smaller the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery, the less electrochemical polarization phenomenon of the air electrode of the zinc-air battery, and thus the better the charge and discharge stability of the air electrode.

[0097] from Fig.12It can be seen from Table 2 that the zinc-air battery using the spinel structure sulfide NiCo2S4 / CS prepared in Example 1 as the cathode catalyst (i.e., the zinc-air battery obtained by Application 1) has a difference ΔE between the initial voltage difference and the final voltage difference of 0.029V, which indicates that the electrochemical polarization phenomenon of the air electrode of the zinc-air battery obtained by Application 1 is very small, and also indicates that the charge and discharge stability of the air electrode is good; in addition, it can be seen from Table 2 that the stable cycle time of the zinc-air battery obtained by Application 1 is about 318 hours, and within 318 hours of the stable cycle, the charge and discharge voltage of the zinc-air battery obtained by Application 1 is basically stable, wherein the discharge voltage is stable at above 1.0V, showing excellent cycle stability, which indicates that the zinc-air battery prepared by Application 1 has a long cycle life and good stability.

[0098] Application 2:

[0099] A method for preparing a zinc-air battery using the air cathode catalyst NiCo2S4 / CS described in Example 2. The difference between the method for preparing a zinc-air battery in Application 2 and the method for preparing a zinc-air battery described in Application 1 is only that the air cathode catalyst NiCo2S4 / CS prepared in Example 2 is used in step S1 of Application 2 instead of the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0100] The zinc-air battery obtained in application 2 is charged and discharged by a charge and discharge instrument at 10 mA·cm -2 The zinc-air battery was tested for constant current charge and discharge at a current density of Fig.12 As shown in Table 2. Fig.12 As can be seen from Table 2, the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery using the spinel sulfide NiCo2S4 / CS prepared in Example 2 as the cathode catalyst (i.e., the zinc-air battery obtained in Application 2) is 0.037 V. This indicates that the electrochemical polarization phenomenon of the air electrode of the zinc-air battery obtained in Application 2 is small, but higher than the polarization phenomenon of the air electrode of the zinc-air battery obtained in Application 1, and the charge and discharge stability of the air electrode of the zinc-air battery obtained in Application 2 is slightly worse than that of the zinc-air battery obtained in Application 1; in addition, it can be seen from Table 2 that the cycle time of the zinc-air battery obtained in Application 2 is stable at about 161 hours.

[0101] Application 3:

[0102] A method for preparing a zinc-air battery using the air cathode catalyst NiCo2S4 / CS described in Example 3. The difference between the method for preparing a zinc-air battery in Application 3 and the method for preparing a zinc-air battery described in Application 1 is only that the air cathode catalyst NiCo2S4 / CS prepared in Example 3 is used in step S1 of Application 3 instead of the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0103] The zinc-air battery obtained in application 3 is charged and discharged by a charge and discharge instrument at 10 mA·cm -2 The zinc-air battery was tested for constant current charge and discharge at a current density of Fig.12 As shown in Table 2. Fig.12 As can be seen from Table 2, the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery using the spinel sulfide NiCo2S4 / CS prepared in Example 3 as the cathode catalyst (i.e., the zinc-air battery obtained by Application 3) is 0.039 V. This indicates that the electrochemical polarization phenomenon of the air electrode of the zinc-air battery obtained by Application 3 is small, but higher than the polarization phenomenon of the air electrode of the zinc-air battery obtained by Application 1, and the charge and discharge stability of the air electrode of the zinc-air battery obtained by Application 3 is slightly worse than that of the zinc-air battery obtained by Application 1; in addition, it can be seen from Table 2 that the cycle time of the zinc-air battery obtained by Application 3 is stable at about 163 hours.

[0104] Comparative Application I:

[0105] A method for preparing a zinc-air battery using the three-dimensional porous rod-shaped carbon sponge CS described in Comparative Example 1. The difference between the method for preparing a zinc-air battery in Comparative Application Ⅰ and the method for preparing a zinc-air battery described in Application 1 is only that the three-dimensional porous rod-shaped carbon sponge CS used in step S1 of Comparative Application Ⅰ replaces the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0106] The zinc-air battery obtained in the comparative application I was charged and discharged by a charge and discharge instrument at 10 mA·cm -2 The zinc-air battery was tested for constant current charge and discharge at a current density of Fig.12 As shown in Table 2. Fig.12It can be seen from Table 2 that the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery using the three-dimensional porous rod-shaped carbon sponge CS prepared in Comparative Example 1 as the cathode catalyst (i.e., the zinc-air battery obtained by Comparative Application Ⅰ) is 0.068V, indicating that the electrochemical polarization phenomenon of the air electrode of the zinc-air battery obtained by Comparative Application Ⅰ is more obvious than that of the air electrode of the zinc-air battery obtained by Application 1; in addition, it can be seen from Table 2 that the cycle time of the zinc-air battery obtained by Comparative Application Ⅰ is stable at about 30 hours, indicating that the zinc-air battery obtained by Comparative Application Ⅰ can be stably cycled for a shorter time.

[0107] Comparative Application II:

[0108] A method for preparing a zinc-air battery using the sulfide NiCo2S4 described in Comparative Example 2. The difference between the method for preparing a zinc-air battery in Comparative Application II and the method for preparing a zinc-air battery described in Application 1 is only that the sulfide NiCo2S4 used in step S1 of Comparative Application II replaces the air cathode catalyst NiCo2S4 / CS prepared in Example 1.

[0109] The zinc-air battery obtained in the comparative application II is charged and discharged by a charge and discharge instrument at 10 mA·cm -2 The zinc-air battery was tested for constant current charge and discharge at a current density of Fig.12 As shown in Table 2. Fig.12 It can be seen from Table 2 that the difference ΔE between the initial voltage difference and the final voltage difference of the zinc-air battery using the sulfide NiCo2S4 prepared in Comparative Example 2 as the cathode catalyst (i.e., the zinc-air battery obtained by Comparative Application II) is 0.054V, indicating that the electrochemical polarization phenomenon of the air electrode of the zinc-air battery obtained by Comparative Application II is more obvious than that of the zinc-air battery obtained by Application 1; in addition, it can be seen from Table 2 that the cycle time of the zinc-air battery obtained by Comparative Application II is stable at about 36 hours, indicating that the zinc-air battery obtained by Comparative Application II can be stably cycled for a shorter time.

[0110] Table 2:

[0111] Types of zinc-air batteries <![CDATA[ΔE=ΔE 初 -ΔE 末 ]]> Battery stable cycle time Application 1 0.029V 318h Application 2 0.037V 161h Application 3 0.039V 163h Comparative Application I 0.068V 30h Comparative Application Ⅱ 0.054V 36h

[0112] In summary, the air cathode catalyst NiCo2S4 / CS prepared in the present application has excellent cycle stability and is very suitable for the preparation of zinc-air batteries.

[0113] In addition, the following conclusions can be drawn by combining the test results of Table 1 and Table 2: It can be seen from Table 1 that the amount of sulfide NiCo2S4 loaded on the three-dimensional porous rod-shaped carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 of the present application is smaller than that in Example 2, and larger than that in Example 3. It can be seen from Table 2 that the stable cycle time of the zinc-air battery using the air cathode catalyst NiCo2S4 / CS prepared in Example 1 as the cathode catalyst (i.e., the zinc-air battery obtained by Application Ⅰ) is longer than that of the zinc-air battery using the air cathode catalyst NiCo2S4 / CS prepared in Example 2 as the cathode catalyst (i.e., the zinc-air battery obtained by Application Ⅱ) and the zinc-air battery using the air cathode catalyst NiCo2S4 / CS prepared in Example 3 as the cathode catalyst (i.e., the zinc-air battery obtained by Application Ⅲ). This is mainly due to: the air cathode of the zinc-air battery undergoes an oxygen reduction reaction, and during the reaction, the O2 molecules on the surface of the cathode catalyst will accept electrons provided by Ni atoms, Co atoms and the three-dimensional porous rod-shaped carbon sponge CS, and be converted into hydrogen oxide intermediates (OOH- or ); During the oxygen reduction reaction at the air cathode, when the loading amount of sulfide NiCo2S4 on the three-dimensional porous rod-shaped carbon sponge CS is too small, the cathode catalyst (i.e., the air cathode catalyst NiCo2S4 / CS of the present application) will not be able to provide enough electrons, thereby making it difficult for the air cathode to continue the oxygen reduction reaction; and when the amount of sulfide NiCo2S4 / CS loaded on the three-dimensional porous rod-shaped carbon sponge CS is too much, the sulfide NiCo2S4 crystal particles will aggregate on the surface and / or in the pores of the three-dimensional porous rod-shaped carbon sponge CS, thereby causing some pores of the three-dimensional porous rod-shaped carbon sponge CS to be blocked, and the blockage of some pores of the three-dimensional porous rod-shaped carbon sponge CS will cause the specific surface area of ​​the air cathode catalyst NiCo2S4 / CS to decrease and the transmission channels of zinc ions to decrease, thereby affecting the stability of the zinc-air battery cycle. That is to say, since an appropriate amount of sulfide NiCo2S4 is loaded on the three-dimensional porous rod-shaped carbon sponge CS in the air cathode catalyst NiCo2S4 / CS prepared in Example 1 of the present application, the zinc-air battery using the air cathode catalyst NiCo2S4 / CS prepared in Example 1 as the cathode catalyst (i.e., the zinc-air battery obtained by Application Ⅰ) obtains a longer stable cycle time.

[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. An air cathode catalyst NiCo2S4 / CS, characterized in that: The air cathode catalyst NiCo2S4 / CS comprises a three-dimensional porous rod-shaped carbon sponge CS and NiCo2S4 nanocrystalline particles supported on the three-dimensional porous rod-shaped carbon sponge CS.

2. The air cathode catalyst NiCo2S4 / CS according to claim 1, characterized in that: The three-dimensional porous rod-shaped carbon sponge CS has a rod-shaped structure with pores; the NiCo2S4 nanocrystalline particles are loaded on the surface and pores of the three-dimensional porous rod-shaped carbon sponge CS.

3. A method for preparing an air cathode catalyst NiCo2S4 / CS, characterized in that: The air cathode catalyst NiCo2S4 / CS is the air cathode catalyst NiCo2S4 / CS according to any one of claims 1 to 2; the preparation method of the air cathode catalyst NiCo2S4 / CS comprises the following steps: S1. dissolving aluminum nitrate nonahydrate and 1,4-naphthalenedicarboxylic acid in deionized water to obtain solution I; S2, ultrasonically homogenizing solution I and then performing a hydrothermal reaction to obtain a mixture A; S3, centrifuging the mixture A to obtain a light yellow precipitate, washing the light yellow precipitate and vacuum drying it to obtain a dried precipitate; S4, calcining the dried precipitate under a nitrogen atmosphere to obtain a rod-shaped aluminum-based metal organic framework precursor; S5, mixing a rod-shaped aluminum-based metal organic framework precursor with hydrofluoric acid, and ultrasonically etching for 40 minutes to obtain a mixture B; centrifugally washing the mixture B to obtain a neutral aluminum-based metal organic framework, and drying the neutral aluminum-based metal organic framework to obtain a three-dimensional porous rod-shaped carbon sponge CS; S6, ultrasonically dispersing the three-dimensional porous rod-shaped carbon sponge CS in a mixed solution obtained by mixing ethanol and deionized water to obtain solution II; adding cobalt acetate tetrahydrate and nickel acetate tetrahydrate to solution II, and then heating and stirring under condensation reflux conditions, and then adding ammonia water, and continuing to stir under condensation reflux conditions to obtain solution III; S7. Add thiourea to solution III, continue stirring under condensation reflux conditions to obtain solution IV; subject solution IV to a hydrothermal reaction to obtain a mixture C, and then, centrifuge and wash the mixture C, and then freeze-dry it for 24 hours to obtain an air cathode catalyst NiCo2S4 / CS.

4. The method for preparing an air cathode catalyst NiCo2S4 / CS according to claim 3, characterized in that: In step S4, before calcining the dried precipitate in a nitrogen atmosphere, the dried precipitate is first ground into powder to obtain precipitate powder, and then the precipitate powder is calcined in a nitrogen atmosphere.

5. The method for preparing an air cathode catalyst NiCo2S4 / CS according to claim 3, characterized in that: In step S1, in solution I, the molar ratio of aluminum nitrate nonahydrate, 1,4-naphthalene dicarboxylic acid and deionized water is (1-3):(0.5-2):(1000-1200).

6. The method for preparing an air cathode catalyst NiCo2S4 / CS according to claim 3, characterized in that: In step S6, the volume ratio of ethanol to deionized water is (55-60):(2-4), and the mass percentage concentration of ethanol is 99.5%; the molar ratio of cobalt acetate tetrahydrate, nickel acetate tetrahydrate and thiourea is (1-3):(0.5-2):(5-7); and the mass percentage concentration of ammonia water is 25%-28%.

7. Application of air cathode catalyst NiCo2S4 / CS as cathode catalyst in zinc-air battery, characterized in that: The air cathode catalyst NiCo2S4 / CS is the air cathode catalyst NiCo2S4 / CS as described in claims 1 to 2.

8. A method for preparing a zinc-air battery using an air cathode catalyst NiCo2S4 / CS, characterized in that: The air cathode catalyst NiCo2S4 / CS is the air cathode catalyst NiCo2S4 / CS according to claims 1 to 2; the method for preparing a zinc-air battery using the air cathode catalyst NiCo2S4 / CS comprises the following steps: a) Preparation of cathode catalyst: Nafion ethanol solution, air cathode catalyst NiCo2S4 / CS and conductive carbon are mixed, and then ultrasonically treated to obtain cathode catalyst suspension; b) Preparation of air cathode: Place carbon paper on a constant temperature heating pad, spray the cathode catalyst suspension prepared in step S1 on the hydrophilic layer of the carbon paper, and let it stand for a period of time to obtain an air cathode; c) Preparation of electrolyte: Mix deionized water, KOH solution and zinc acetate solution, and stir until dissolved to obtain an electrolyte for a zinc-air battery; d) Assembly of zinc-air battery: Assemble the zinc-air battery mold, air cathode, zinc sheet anode electrode and electrolyte together to obtain the zinc-air battery.

9. The method for preparing a zinc-air battery using an air cathode catalyst NiCo2S4 / CS according to claim 8, characterized in that: In step a), the ratio of the volume μL of the nafion ethanol solution to the mass mg of the air cathode catalyst NiCo2S4 / CS is (700-800):(2-4); the mass ratio of the air cathode catalyst NiCo2S4 / CS and the conductive carbon is (2-4):(0.5-1.5); the mass percentage concentration of ethanol in the nafion ethanol solution is 0.1%; the mass percentage concentration of the ethanol solution is 0.1%.

10. A zinc-air battery, characterized in that: The zinc-air battery is prepared by the method for preparing a zinc-air battery using an air cathode catalyst NiCo2S4 / CS as described in claims 8 to 9.